2021
DOI: 10.3390/agriculture11010044
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Increase in Soil Moisture Storage Capacity and Nutrient Enhancement of Different Organic Amendments in Paddy Soil

Abstract: Increasing soil moisture storage capacity is a strategy that can be implemented to minimize the use of water in paddy rice cultivation. Organic materials from different sources have the potential to increase soil moisture storage and nutrient enrichment. An incubation study was conducted to evaluate the incorporation of five selected organic amendments—as follows: rice husk biochar (RHB), oil palm empty fruit bunch biochar (EFBB), compost (COMP), rice husk ash (RHA), and oil palm bunch ash (PBA), with a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…We believe this increased K concentration in the soil resulted from the applied K with the biochar's ash. Many researchers have also reported similar results [32,58,59]. For instance, in tropical acid soil, soil exchangeable K increased using 5 t ha −1 chicken litter biochar [60].…”
Section: Biochar and Lime Treatment Affects Soil Propertiesmentioning
confidence: 58%
“…We believe this increased K concentration in the soil resulted from the applied K with the biochar's ash. Many researchers have also reported similar results [32,58,59]. For instance, in tropical acid soil, soil exchangeable K increased using 5 t ha −1 chicken litter biochar [60].…”
Section: Biochar and Lime Treatment Affects Soil Propertiesmentioning
confidence: 58%
“…Sun and Liu [126] observed that, depending on the application rate of straw, biochar increased the water content up to 18.4%, and woodchips biochar enhanced water-holding capacity upto 6.8% compared to control in a Vertisol clay soil. In clay soil, an increase of available water capacity with an increment rate of biochar reported by Kameyama et al [169]; further addition of biochar increased gravimetric water content in clay-textured paddy soil, also reported by Haque et al [170]. In some studies, there were no significant changes in soil water storage due to biochar application, presented in Table 9 [128,134].…”
Section: Soil Water Retention Propertiesmentioning
confidence: 75%
“…This improved moisture retention might be explained by SEM micrographs of RHB and EFBB (Figure 2). The figures of RHB and EFBB revealed the presence of different sized micropores, and these pores could be served as a capillary store of water [40]. However, RHB did not show porous properties as EFBB did, possibly due to the different feedstock and divergence in temperature during the biochar preparation.…”
Section: Irrigation Water Usage and Productivitymentioning
confidence: 94%
“…The soil belongs to the clay textural class (sand 6.60%, silt 29.62% and clay 63.79%) according to USDA taxonomy [40]. The pH of the soil was measured by a glass electrode digital pH meter from the 1:2.5 ratio soil and water solution [41].…”
Section: Collection and Analysis Of Soil And Biochar Samplesmentioning
confidence: 99%
See 1 more Smart Citation